New phospholipid Fatty acids from the Marine sponge Cinachyrella alloclada Uliczka. - Barnathan, G.; Miralles, J.; Gaydou, E.M.; Boury-Esnault, N; Kornprobst, J.-M. (Lipids, 1992)
The fatty acid composition of phospholipids from the Senegalese spongeCinachyrella alloclada was examined. Two new fatty acids not hitherto found in nature, namely 10,13-octadecadienoic acid and 16-tricosenoic acid, were identified. 8-Hexadecenoic, 13-nonadecenoic and 5,9,13-trimethyltretradecanoic fatty acids were also found for the first time in sponges. The latter compound (1.4% of the total fatty acid mixture), an isoprenoid fatty acid, accompanies the major fatty acid 4,8,12-trimethyltridecanoic acid (19.7%). The monomethyl branched fatty acids (22%) identified include 23-methylpentacosanoic acid (anteiso-26:0), not previously observed in sponged. The major long-chain fatty acids encountered were the known 17-tetracosenoic 19-heptacosadienoic and 5,9,23-tricontatrienoic acid. Some sixty fatty acids were identified as methyl esters andN-acyl pyrrolidides by gas chromatography and gas